2017
DOI: 10.7771/2157-9288.1131
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Differences in Out-of-School High School Science Experiences and Influence on Students’ Engineering Choices

Abstract: Participation from a variety of students is important to the long-term growth of the engineering field. Much of the research on engineering recruitment or career choice has focused on engineering as a whole, even though engineering disciplines are varied in student participation and focus. This work examines how students' out-of-school interests and experiences in high school predict the likelihood of choosing a career in a particular engineering discipline. Out-of-school experiences offer more unstructured wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…For example , Beymer, Rosenberg, Schmidt, and Naftzger (2018) suggest that there is a positive relationship between affect and engagement in OST activities focusing on STEM (e.g., summer programs) among adolescents. Similarly, other studies have shown that there is a significant, positive relationship of participation in math or science clubs to STEM GPA and interest among adolescents (Godwin et al, 2016;Gottfried & Williams, 2013;Guest & Schneider, 2003). Meanwhile, college students' STEM career interest is associated with their science-focused OST program participation back in middle and high school, demonstrating a lasting relationship between OST learning experience and later interest in STEM fields (Dabney et al, 2012;Young et al, 2016).…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…For example , Beymer, Rosenberg, Schmidt, and Naftzger (2018) suggest that there is a positive relationship between affect and engagement in OST activities focusing on STEM (e.g., summer programs) among adolescents. Similarly, other studies have shown that there is a significant, positive relationship of participation in math or science clubs to STEM GPA and interest among adolescents (Godwin et al, 2016;Gottfried & Williams, 2013;Guest & Schneider, 2003). Meanwhile, college students' STEM career interest is associated with their science-focused OST program participation back in middle and high school, demonstrating a lasting relationship between OST learning experience and later interest in STEM fields (Dabney et al, 2012;Young et al, 2016).…”
mentioning
confidence: 77%
“…Beneficial opportunities of STEM learning come in a number of intentional ways in the academic curriculum, including in activities out of the classroom. Out-of-school time (OST) experiences may be an effective venue to enrich students' learning experiences and promote STEM interest (Dabney et al, 2012;Godwin, Sonnert, & Sadler, 2016;Price, Kares, Segovia, & Loyd, 2018). OST programs are adult-supervised, extracurricular activities taking place in a structured or unstructured manner, such as after-school programs and summer camps.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Structural Equation Model of First-Generation College Students' Out-of-School Experiences with physics and STEM interest, recognition, and identity. Prior research has found that out-of-school learning environments play an important role in promoting and building interest and over time supporting STEM identities [4], [47]- [49]. Additionally, another study found that students who persisted in engineering had meaningful experiences (i.e., summer camps, competitions, etc.)…”
Section: Discussionmentioning
confidence: 99%